Barriers to Sexual Health Education for Female Adolescents in Schools from Health Care Providers' perspective - Sanaz Zangeneh Jolovi; Mohhamad Javad Tarrahi; Faranak Safdari Dehsheshmeh; Nafiseh Sadat Nekuei (Mashhad University of Medical Sciences, 2023)
Background & aim: Sexual health education to female adolescents in schools is one of the most challenging topics in most parts of the world. This study investigated the barriers to sexual health education for female adolescents in schools from health care providers' perspective.Methods: This descriptive cross-sectional study was performed on 200 health care providers in the comprehensive health center of Isfahan from October 2019 to October 2020, who were selected using multistage sampling. A valid and reliable researcher-made questionnaire including five sections and 28 questions was used to assess the barriers to sexual health education in areas including individual domain related to the health care providers and female adolescents as well as organizational and socio-cultural domains. Data were analyzed using descriptive statistics.Results: The most important barriers to sexual health education for female adolescents included insufficient knowledge of health care providers (59%), lack of appropriate communication skills with female adolescents (59.5%) and conflict of sexual education to female adolescents with cultural beliefs of society (56.5%). Among the four domains studied, organizational (31.4±4.93) and socio-cultural domain (27.1±5.12) barriers had higher mean scores.Conclusion: Insufficient knowledge and skills of health care providers and conflict of sexual education to female adolescents with cultural beliefs of society are the most important barriers to sexual health education for this population. Training of the health team as well as education and culture building in the community for families and the general public can be effective to remove barriers to sexual education for female adolescents.